2014
DOI: 10.1108/imds-01-2014-0013
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of ISO 9001: a longitudinal survey

Abstract: Purpose – The purpose of this paper is to analyze the influence of the motivation to adopt International Standards Organization (ISO) 9001 on both the internalization of the standard, namely the active day-to-day use of its main underlying practices, and the benefits obtained from its adoption. Similarly, the influence of the internalization on the benefits derived from ISO 9001 is analyzed. Design/methodology/approach – A longitudinal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 24 publications
3
64
0
9
Order By: Relevance
“…Additionally, Kawai, Strange, and Zucchella () found that a proactive approach to environmental management led firms to better identify potential sources of improvement for CEP. This type of effect has also been found for other meta‐standards such as ISO 9001 (e.g., Allur, Heras‐Saizarbitoria, & Casadesus, ; Bello‐Pintado, Heras‐Saizarbitoria, & Merino‐Díaz‐de‐Cerio, ; Heras‐Saizarbitoria & Boiral, ; Tari, Heras‐Saizarbitoria, & Pereira, ). Then, the following hypothesis (H6) is proposed:H6 The influence of the firm's EMS certification (e.g., ISO 14001 and EMAS) on improved CEP is moderated by the level of internalization of the certified EMS.…”
Section: Literature Reviewsupporting
confidence: 69%
“…Additionally, Kawai, Strange, and Zucchella () found that a proactive approach to environmental management led firms to better identify potential sources of improvement for CEP. This type of effect has also been found for other meta‐standards such as ISO 9001 (e.g., Allur, Heras‐Saizarbitoria, & Casadesus, ; Bello‐Pintado, Heras‐Saizarbitoria, & Merino‐Díaz‐de‐Cerio, ; Heras‐Saizarbitoria & Boiral, ; Tari, Heras‐Saizarbitoria, & Pereira, ). Then, the following hypothesis (H6) is proposed:H6 The influence of the firm's EMS certification (e.g., ISO 14001 and EMAS) on improved CEP is moderated by the level of internalization of the certified EMS.…”
Section: Literature Reviewsupporting
confidence: 69%
“…Once the benefits of having an operating QMS in place have been reaped out, bearing the costs of the certification does no longer make sense. Thus, companies that have internalised their QMS, do not need the certificate anymore and may decide to abandon it, keeping the QMS in place (Bernardo and Simon, 2014;Allur, Heras-Saizarbitoria and Casadesús, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The main reason to adopt was explained in terms of image and prestige. The subsequent editions of the standard were more focused on customer satisfaction, and the reasons that lead organizations to certify evolved into seeking customer satisfaction [47]. This case demonstrates how the standard adapts to the necessities and requirements of the organizations.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 92%